2017
DOI: 10.1111/1467-8268.12286
|View full text |Cite
|
Sign up to set email alerts
|

Input Policies and Crop Diversification: Evidence from the Collines Region in Benin

Abstract: Formulating policy to strengthen rural livelihood in a country like Benin may be very challenging. This paper investigates the effect of input policies on crop diversification in rural Benin. Multistage sampling techniques have been used to collect primary data from 522 households in the Collines Region. Considering access to fertilizer and seed policies, we used a linear regression analysis to find that access to fertilizer and seed negatively affect the extent of crop diversification. Although some factors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Similar positive relationships were also verified by Dorsey () in Kenya, Chibwana, Fisher, and Shively () in Malawi, McCord et al () in semiarid agricultural systems near Mount Kenya, Hitayezu, Zegeye, and Ortmann () in South Africa, and Shahbaz, Boz, and Haq () in Pakistan. Contrary to this, Adjimoti et al () found out that in Benin, larger land holdings were associated with lower diversification, mainly due to the fact that large farm size holders tended to diversify into high‐value crops and then specialise on this crop (e.g., cashew cultivation). In fact, Birthal et al () considers that large‐scale farmers are often better able to bear the risks associated with the production and marketing of high‐value commodities than small‐scale farmers.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Similar positive relationships were also verified by Dorsey () in Kenya, Chibwana, Fisher, and Shively () in Malawi, McCord et al () in semiarid agricultural systems near Mount Kenya, Hitayezu, Zegeye, and Ortmann () in South Africa, and Shahbaz, Boz, and Haq () in Pakistan. Contrary to this, Adjimoti et al () found out that in Benin, larger land holdings were associated with lower diversification, mainly due to the fact that large farm size holders tended to diversify into high‐value crops and then specialise on this crop (e.g., cashew cultivation). In fact, Birthal et al () considers that large‐scale farmers are often better able to bear the risks associated with the production and marketing of high‐value commodities than small‐scale farmers.…”
Section: Resultsmentioning
confidence: 94%
“…Shahbaz et al (), found, however, that self‐owned operated farms in Punjab region in Pakistan were less likely to undertake crop diversification than other forms of tenure, such as renters and shareholders, but they do not explain why. In Benin, Adjimoti et al () observed that female‐headed households are less likely to diversify into agroforestry because of the traditional land tenure system, which is favourable to men.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations